Kemampuan Kerja Dan Pengaruhnya Terhadap Kinerja Karyawan PT. Mitra Pinasthika Mustika Motor Pekanbaru - Asnahwati, Asnahwati (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research was conducted at PT. Pinasthika Mustika Motor Pekanbaru Partner. The aim of this research is to find out whether work ability influences employee performance at PT. Pinasthika Mustika Motor Pekanbaru Partner. The population in this study was 50 people. This research took samples using a saturated sampling technique, namely the entire population was sampled, namely 50 people. The data used is primary and secondary data with analysis using simple linear regression. The results of the research found that the regression equation was Y=17.614+ 0.617X and the value obtained was t_count > t_tabel (7.129 > 2.01063) with a significance value of 0.00 < 0.05 so that H_0 was rejected and H_a was accepted or it could be concluded that work ability had a positive effect on employee performance at PT. Pinasthika Mustika Motor Pekanbaru Partner. The results of the coefficient of determination obtained an R_square value or coefficient of determination of 0.514, which means the magnitude of the influence of the independent variable (work ability) on the dependent variable (employee performance) at PT. Mitra Pinasthika Mustika Motor Pekanbaru was 51.4 percent while the remaining 48.6 percent was influenced by other independent variables that were not observed in this research, such as compensation, work environment, etc